Anomalous origin of a right pulmonary artery identified with echocardiography combined with CT: a case in a juvenile patient - Yan-ling Li; Ping Xie; Jia Wei; Zhao-xia Guo (Journal of Cardiothoracic Surgery)
Abstract An anomalous origin of the pulmonary artery (AOPA) from the ascending aorta is a relatively rare but important cardiac malformation that frequently involves the right pulmonary artery (RPA). Its clinical manifestations depend mainly on the associated significant pulmonary hypertension, with an extremely high mortality rate in the first year of life. Here, we present a rare survival case of an 11-year-old child with the disease, who was hospitalized due to intermittent abdominal pain, but without any apparent signs of chest tightness or shortness of breath. The low oxygen saturation as discovered during the physical examination. Subsequent examination with transthoracic echocardiography (TTE) and pulmonary artery computed tomography angiography (CTA) revealed this unexpected congenital malformation. Although the estimated mean pulmonary artery pressure (MAP) from the TTE was 51 mmHg, which seemed to contraindicate corrective cardiac surgery, the limitations of TTE were considered. Consequently, after multidisciplinary consultation, surgical intervention was ultimately decided upon, resulting in a favorable prognosis for the patient. This case provides a new insight for clinicians in the diagnosis and treatment of complex congenital heart diseases.